Tigers! Have a great day!
Answer:
10
Step-by-step explanation:
<u><em>y = -4 </em></u>
<u><em>x = 6 </em></u>
<em><u>x-y = 6-(-4) = 6+4 = 10</u></em>
<em><u /></em>
Answer:
<h3>⇒ A. 2 should be distributed as 2y + 12, y = 6</h3>
Step-by-step explanation:
Here are the steps to solve this equation:
<u>Given:</u>
First step: 2(y+6)-4y
Use the distributive property.
<u>Distributive property:</u>
<h3>
⇒ A(B+C)=AB+AC</h3>
2(y+6)
2*y=2y
2*6=12
2y+12
Isolate the term of y from one side of the equations.
2y+12=4y
Subtract by 12 from both sides.
2y+12-12=4y-12
Solve.
2y=4y-12
Then, you subtract by 4y from both sides.
2y-4y=4y-12-4y
Solve.
2y-4y=-2y
-2y=-12
Divide by -2 from both sides.
![\sf{\dfrac{-2y}{-2}=\dfrac{-12}{-2}}](https://tex.z-dn.net/?f=%5Csf%7B%5Cdfrac%7B-2y%7D%7B-2%7D%3D%5Cdfrac%7B-12%7D%7B-2%7D%7D)
Solve.
Divide the numbers from left to right.
<u>Solutions:</u>
-12/-2=6
![\Longrightarrow: \boxed{\sf{y=6}}](https://tex.z-dn.net/?f=%5CLongrightarrow%3A%20%5Cboxed%7B%5Csf%7By%3D6%7D%7D)
- <u>Therefore, the correct answer is A. "2 should be distributed as 2y+12, y=6".</u>
I hope this helps. Let me know if you have any questions.
Sureeeee brainliest pleasee
Your answers is for sure 5